PENGEMBANGAN MEDIA MOBILE LEARNING BERBASIS ANDROID DASAR PROGRAMMABLE LOGIC CONTROLLER PADA MATA PELAJARAN INSTALASI MOTOR LISTRIK SEBAGAI SUPLEMEN PEMBELAJARAN SISWA - Neni Astika; Muhammad Amin (Journal of Electrical Vocational Teacher Education (JEVTE), 2022)
AbstractThe purpose of this study is to develop android-based Mobile learning media Basic Programmable Logic Controller in the Subject of Electric Motor Installation as a Learning Supplement for Class XI (TITL) Students of Sinar Husni Private Vocational School 2 TR Labuhan Deli using Adobe Flash CS6, validating android-based Mobile learning media. Basic Programmable Logic Controller in Electric Motor Installation Subjects as a Learning Supplement for Class XI (TITL) Students of Sinar Husni Private Vocational School 2 TR Labuhan Deli using Adobe Flash CS6. The research results are in the form of android-based mobile learning media development procedures that have been successfully compiled with the type of research and development or R&D using the ADDIE development model (analysis, design, development, implementation, evaluation). According to Sugiyono, the research and development steps are modified according to the author's needs with seven stages, namely: potential and problems, data collection, product design, design validation, design revsi, product trials, and product revisions. Media developed with adobe flash CS6 program and assisted with other programs kinemaster, the feasibility of android-based mobile learning media by material experts gets 85% with the category "very feasible”Abstract must reflect the overall substance of the article content and be able to help readers determine its relevance to their interests and decide whether to read the document in its entirety. Eligibility assessment by linguists 89.28 % with the category "very worthy". The feasibility assessment by media experts got 86.45% with the category "very feasible". Based on respondents users / media users by electric motor installation teachers got 93.75% with the category of "very feasible" and the assessment of trials from students on a small scale got 76.70% with the category of "feasible" and in broad-scale trials got 93.96% with the category of "very feasible". So it can be concluded that m-learningandroid is very suitable to be used as a basic learning medium for PLC.Key Words: Mobile Learning, Development, PLC Basics AbstrakTujuan penelitian ini adalah mengembangkan media pembelajaran Mobile learning berbasis android Dasar Programmable Logic Controller Pada Mata Pelajaran Instalasi Motor Listrik Sebagai Suplemen Pembelajaran Siswa Kelas XI (TITL) SMK Swasta Sinar Husni 2 TR Labuhan Deli menggunakan Adobe Flash CS6, memvalidasikan media pembelajaran Mobile learning berbasis android. Dasar Programmable Logic Controller Pada Mata Pelajaran Instalasi Motor Listrik Sebagai Suplemen Pembelajaran Siswa Kelas XI (TITL) SMK Swasta Sinar Husni 2 TR Labuhan Deli menggunakan Adobe Flash CS6. Hasil penelitian berupa prosedur pengembangan media mobile learning berbasis android yangtelah berhasil disusun dengan jenis peneltian researchand development atau R&D menggunakan model pengembangan ADDIE (analysis, design, development, implementation, evaluation). Langkah-langkah penelitian dan pengembangan menurut Sugiyono yang dimodifikasi sesuai kebutuhan penulis dengan tujuh tahapan yaitu : potensi dan masalah, pengumpulan data, desain produk, validasi desain, revsi desain, uji coba produk, dan revisi produk. Media dikembangkan dengan program adobe flash CS6 dan dibantu dengan program lain kinemaster, kelayakan media mobile learning berbasis android oleh ahli materi mendapatkan 85 % dengan kategori ”sangat layak”.Penilaian kelayakan oleh ahli bahasa 89,28 % dengan kategori “sangat layak”. Penilaian kelayakan oleh ahli media mendapatkan 86,45 % dengan kategori “sangat layak”. Berdasarkan responden pengguna/user media oleh guru instalasi motor listrik mendapatkan 93,75 % dengan kategori “sangat layak” dan penilaian uji coba dari peserta didik pada skala kecil mendapatkan 76,70 % dengan kategori “layak” serta pada uji coba skala luas mendapatkan 93,96 % dengan kategori “sangat layak”. Jadi dapat di simpulkan m-learningandroid sangatlayak digunakan sebagai media pembelajaran dasar PLC. Kata Kunci: Mobile Learning, Pengembangan, Dasar PLC